2021
DOI: 10.1108/pm-01-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental orientation, green marketing mix and social capital on the competitive advantage of real estate developers in Bali

Abstract: PurposeTo test and explain about the implementation of the green marketing mix strategy, based on an environmental orientation and social capital in increasing the competitive advantage of the real estate developer or company in Bali.Design/methodology/approachData collected in this study are primary data. Primary data collection is done by survey method using a research instrument in the form of a questionnaire. This research was conducted at real estate development companies in several cities in Bali. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
3
18
0
2
Order By: Relevance
“…Firms with EMS are able to derive significantly better operational efficiencies and greater supply chain optimisation compared to firms without EMS. The findings of the study by [49] indicated that firms with environmental concern, environmental conservation policies, and environmental stewardship responsibilities are able to improve their competitive advantage. The findings indicate that GI and GCA are positively related in support of hypothesis five.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Firms with EMS are able to derive significantly better operational efficiencies and greater supply chain optimisation compared to firms without EMS. The findings of the study by [49] indicated that firms with environmental concern, environmental conservation policies, and environmental stewardship responsibilities are able to improve their competitive advantage. The findings indicate that GI and GCA are positively related in support of hypothesis five.…”
Section: Discussionmentioning
confidence: 97%
“…This can lead to the development of green products and services that are difficult to imitate and improve a firm's green competitive advantage. In addition, EEO focuses on how a firm fulfils the expectations of external stakeholders on environmental issues [49]. This can lead to the development of green products that are difficult to imitate but meet the green expectation of customers.…”
Section: Environmental Orientation (Eo and Green Competitive Advantage (Gca)mentioning
confidence: 99%
“…These associations must be studied as the world needs robust research to cope with the rising environmental degradation or, say, pollution (Bhardwaj et al, 2020;Zhang et al, 2019;Kumar, 2016). The emerging economies around the globe are working towards strengthening research in the green (sustainable) production and consumption domain (Giantari & Sukaatmadja, 2021;Amoaka et al, 2020). Hence, India being a major emerging economy in Asia and the world, needs such research that would have scope across different emerging economies.…”
Section: Methodsmentioning
confidence: 99%
“…Even low-income households are reported to have initiated green product consumption (Al Mamun et al, 2018). Multinationals, as well as domestic units across the globe, are hence using green production as well as marketing as a tool to gain competitive advantage, maintain firm reputation, earn maximum profit, and engage their consumers and other stakeholders (Giantari & Sukaatmadja, 2021;Baah et al, 2021;Zameer et al, 2020). Even in emerging economies like India, firms adopt green marketing orientation (Chahal et al, 2014;Bailey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, these companies try to make sure that their entire business activities will not pose harmful damage to the environment by re-aligning or re-purposing the process of producing products or services in a greener way (Habib et al, 2022;To and Lam, 2022;Ahmad et al, 2022). In regard with this matter, many companies not only tried their best to ensure that the concept of sustainability business can be achieved, but also these companies always try to ensure that all of these responsible activities will be noted and known to the general public, consumers and target (or potential) consumers in order to boost and enhance both the image and the reputation of the companies on people's mind (Beatson et al, 2020;Giantari and Sukaatmadja, 2021). Therefore, companies always try to actively communicate, inform and promote all of these "green" activities to the audiences and consumers using all available marketing platforms in order to relay all of these messages effectively (Aldaas et al, 2022;Basu et al, 2022;Padilla and Collazo, 2022).…”
Section: Introductionmentioning
confidence: 99%